Variational Iterative Algorithms in Photoacoustic Tomography with Variable Sound Speed (Journal of Computational Mathematics, 2018)
In this paper, we investigate the adjoint equation in photoacoustic tomography with variable sound speed, and propose three variational iterative algorithms. The basic idea of these algorithms is to compute the original equation and the adjoint equation iteratively. We present numerical examples and show the well performance of these variational iterative algorithms.
Keywords: Photoacoustic Tomography; Variational iterative algorithms.